Efficacy and safety of voriconazole and caspofungin for the treatment of invasive pulmonary aspergillosis in critically ill patients in China - Li, Zhuo; Zong, Yuan; Chen, Dayu; Ma, Juan; Zhang, Peng; Cao, Lu (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo compare and analyze the efficacy and safety of different antifungal drug treatment regimens for patients with invasive pulmonary aspergillosis (IPA) in the intensive care unit (ICU).MethodsWe retrospectively collected the clinical data of patients with IPA in the ICU in two grade-A tertiary hospitals from January 2019 to January 2024 using the HIS system and compared the clinical efficacy, incidence of adverse drug reactions (ADRs), and all-cause mortality at discharge among different antifungal treatments, such as voriconazole alone, caspofungin alone, and a combination of voriconazole plus caspofungin.ResultsA total of 151 patients were enrolled, including 129 in the monotherapy group (with 92 in the voriconazole subgroup and 37 in the caspofungin subgroup) and 22 in the voriconazole plus caspofungin combination group. Aspergillus fumigatus was the most common pathogenic fungus in patients with IPA, followed by Aspergillus flavus. In terms of clinical efficacy, monotherapy and combination therapy were equally effective (P=0.618), and the efficacy of voriconazole or caspofungin alone and that of voriconazole combined with caspofungin in the treatment of IPA was equivalent (P=0.630). In terms of safety, the total incidence of ADRs in the combination therapy group was greater than that in the monotherapy group, but the difference was not statistically significant (P=0.109). The two groups were also equally safe in terms of causing renal dysfunction, liver dysfunction, visual abnormalities, and hypokalemia. However, compared with the monotherapy group, the combination therapy group exhibited a significantly greater incidence of pancytopenia (P=0.013, P=0.004). The all-cause mortality in the combination therapy group was significantly greater than that in the monotherapy group (P=0.027, P=0.009).ConclusionsVoriconazole is still the preferred treatment for critically ill patients with IPA, and caspofungin has good clinical efficacy and safety and can effectively replace voriconazole for these patients. However, the combination treatment with voriconazole and caspofungin did not improve the all-cause mortality rate of critically ill patients with IPA, is associated with increased total ADR and pancytopenia incidence and is not recommended as an initial treatment plan.